Praññʻ thoṅʻ cu Mranʻ mā Nuiṅʻ ṅaṃ toʻ Nuiṅʻ ṅaṃ toʻ Ṅrimʻ vapʻ Pi prāʺ mhu Taññʻ chokʻ reʺ ʼA phvaiʹ ka ʼa sacʻ tī thvaṅʻ praṭṭhānʻʺ chakʻ kapʻ lhū dānʻʺ so sāsanā pru bhvaiʹ taṃ chipʻ toʻ nhaṅʻʹ kammaṭṭhānʻʺ naññʻʺ pra bhvaiʹ taṃ chipʻ toʻ ra cha rā toʻ myāʺ e* theruppattikathā (Sāsanā reʺ Vanʻ krīʺ Ṭhāna, 1994)
Biographies of Burmese Buddhist priests conferred with honorific religious titles by the State Law and Order Restoration Council, Burma.